Group Identity and Groupness: Student Experiences at University - Elliker, Florian; Kotze, P. Conrad; Coetzee, Jan K. (Qualitative Sociology Review, 2017)
One of the key transformations South African universities have undergone in the past two decades is the increase of racial and ethnic diversity of their student bodies and academic staff. In this study, we seek to contribute to a better understanding of these transformation processes by presenting students’ narratives of how they experience the interracial integration of student residences. We first address the potential groupist and essential underpinnings of ethno-racial identifications by situating our categories of analysis in a social-constructivist framework, underlining the situational and processual character of identifying and establishing “groupness,” while simultaneously considering the obdurate quality habitualized ways of identifying may generate. We then present an overview of our sensitizing themes as they are discussed in the literature on race and ethnicity with a focus on South Africa and student experiences. Thirdly, the article introduces the reader to the institutional context of the case study, namely, the campus of the University of the Free State and its student residences. Based on focus group discussions and thematic analyses, we present our findings in the form of the cultural themes that are central to the students’ narrations of their experiences. These themes include the salience of racial and ethnic identifications, tolerant distance, confusion, fairness, neutrality, ethnolinguistic recognition, regional public arenas, rural-urban divides, as well as socio-economic divides.